Designing a radio frequency controlled biomimetic flying bird - Adnan, Nahid Hasan; Alam, Mohammad Talha Talkin (BRAC University, 2014)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2014.